Increased number of neurons in the cervical spinal cord of aged female rats. - Enrique L Portiansky (Public Library of Science (PLoS), 2011)
In the brain, specific signaling pathways localized in highly organized regions called niches allow the persistence of a pool of stem and progenitor cells that generate new neurons in adulthood. Much less is known about the spinal cord where a sustained adult neurogenesis is not observed. Moreover, there is scarce information concerning cell proliferation in the adult mammalian spinal cord and virtually none in aging animals or humans. We performed a comparative morphometric and immunofluorescence study of the entire cervical region (C1-C8) in young (5 mo.) and aged (30 mo.) female rats. Serum prolactin (PRL), a neurogenic hormone, was also measured. Gross anatomy showed a significant age-related increase in size of all of the cervical segments. Morphometric analysis of cresyl violet stained segments also showed a significant increase in the area occupied by the gray matter of some cervical segments of aged rats. The most interesting finding was that both the total area occupied by neurons and the number of neurons increased significantly with age, the latter increase ranging from 16% (C6) to 34% (C2). Taking the total number of cervical neurons the age-related increase ranged from 19% (C6) to 51% (C3), C3 being the segment that grew most in length in the aged animals. Some bromodeoxyuridine positive-neuron specific enolase negative (BrdU(+)-NSE(-)) cells were observed and, occasionally, double positive (BrdU(+)-NSE(+)) cells were detected in some cervical segments of both young and aged rats groups. As expected, serum PRL increased markedly with age. We propose that in the cervical spinal cord of female rats, both maturation of pre-existing neuroblasts and/or possible neurogenesis occur during the entire life span, in a process in which PRL may play a role.